2020
DOI: 10.3389/fneur.2020.585929
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Tissue Plasminogen Activator in Combination With Mechanical Thrombectomy: Clot Migration, Intracranial Bleeding, and the Impact of “Drip and Ship” on Effectiveness and Outcomes

Abstract: Purpose: Intravenous tissue plasminogen activator (tPA) is indicated prior to mechanical thrombectomy (MT) to treat large vessel occlusion (LVO). However, administration takes time, and rates of clot migration complicating successful retrieval and hemorrhagic transformation may be higher. Given time-to-effectiveness, the benefit of tPA may vary significantly based on whether administration occurs at a thrombectomy-capable center or transferring hospital.Methods: We prospectively evaluated 170 individuals with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
(37 reference statements)
0
14
0
Order By: Relevance
“…10–15 However, results from observational studies were equivocal, with some supporting administrating alteplase before thrombectomy for more distal occlusions, 10–12,14–17 while no such benefit was seen in others. 13,16,18–20…”
mentioning
confidence: 99%
“…10–15 However, results from observational studies were equivocal, with some supporting administrating alteplase before thrombectomy for more distal occlusions, 10–12,14–17 while no such benefit was seen in others. 13,16,18–20…”
mentioning
confidence: 99%
“…Characteristics of the studies that were eligible for the meta-analysis are presented in Table 1. [14][15][16][17][18][19] The mean age of included patients was 71 years, while 51% were women. The mean onset-to-groin puncture time did not differ between the pooled groups of patients receiving IV thrombolysis and those treated with EVT alone (mean difference: −19.93 minutes, 95% CI −115.89 to 76.04; eFigure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Chang et al demonstrated that using IV tPA prior to MT improves functional outcomes [ 44 ]. However, their sample also included patients who were unable to be successfully revascularized following MT.…”
Section: Discussionmentioning
confidence: 99%